Exploring the Uptake, Accumulation, and Distribution of Nitrate in Swiss Chard and Spinach and Their Impact on Food Safety and Human Health - Arancibia-Miranda, N; Arancibia-Miranda, N; Manquian-Cerda, K; Manquian-Cerda, K (Elsevier Ltd, 2025)
Greenhouse vegetable production is often associated with the excessive use of nitrogen fertilizers and a high rate of nitrate accumulation. We evaluated the uptake, translocation, and accumulation of nitrate in chard and spinach under greenhouse conditions with optimal fertilization. The results revealed low levels of nitrate in the leachates and substrates (chard ˃ spinach). The high nitrate concentrations in the root zone of spinach compared to those of chard were correlated with a high rate of accumulation in the stem, aerial fraction, and leaves (p < 0.0001). The nitrate concentration in spinach exceeded the limit established by international regulations by 3-fold. The daily intake of nitrate exceeded the acceptable daily intake (ADI) value in almost all age groups (except 13–19 years). However, in the age group of 1–2 years, the daily intake value (7.87 mg NO3− kg−1) was two times higher than the ADI. To improve the quality of food for children, food contamination monitoring programs must ensure adherence to production standards. © 2024 Elsevier Ltd